Researching identity narratives in cyberspace: some methodological challenges - Macedo, Lurdes (2013)
Cyberspace as a study object entails remarkable challenges to researchers, especially because it is an immaterial and highly changeable environment. This paper addresses some of the methodological challenges faced during a research about Lusophone identity narratives in blogs and sites in Brazil, Mozambique and Portugal, and the outlined strategies to overcome the difficulties found. The first challenge was how to design a Lusophone cyberspace cartography, due to the fact that, on one hand, everyday there are new blogs and new sites online, on the other hand, many of these blogs and sites suddenly disappear. Then, some challenges were faced to conduct the content analyses of the selected blogs and sites. In addition, the study objects were too different to enable the use of a single observation protocol, with pre-established categories. Furthermore, there were some questions to deal with the statistical analyses of the blogs. Initially, the researchers concluded that the statistical analyses, which in some cases depend on the collection of data within the blogs, might inflate the results obtained, for instance the number of visitors, the visitors’ origin and the visit average time. Therefore, the Heisenberg uncertainty principle was a valid methodological concern because the blogs and sites observation probably would change the object behaviour. Finally, a well-known research question was addressed: how to interview the bloggers and the webmasters while minimising the impact of the interview in the blogs’ content production. Having identified and described the challenges faced during the research, the aim of this paper is to discuss some methodological ideas about how to study identity narratives on cyberspace.